Novel and safe single-dose treatment of cutaneous leishmaniasis with implantable amphotericin B-loaded microparticles. (December 2019) - Sousa-Batista, Ariane J.; Pacienza-Lima, Wallace; Ré, Maria Inês; Rossi-Bergmann, Bartira
Abstract: The development of an effective amphotericin B (AmB) topical formulation to replace the systemically toxic injections currently used in cutaneous leishmaniasis (CL) treatment is challenging due to poor absorption through the skin. Aiming at an effective local chemotherapy, we designed PLGA (poly(lactide- co -glycolide acid) microparticles loaded with deoxycholate amphotericin B (d-AmB) for both macrophage intracellular targeting and sustained extracellular release. For that, d-AmB/PLGA microparticles with sizes ranging from 0.5 μm to 20 μm were synthesized and tested both in vitro and in vivo . In vitro, d-AmB/PLGA was more selectively active against intracellular amastigotes of Leishmania amazonensis than free d-AmB (selectivity index = 50 and 25, respectively). In vivo, the efficacy of a single intralesional (i.l) injection with d-AmB/PLGA was determined in early and established BALB/c mouse ear lesions. In early lesions, a single injection given on day 10 of infection was more effective in controlling parasite growth than eight i.l. injections with free d-AmB, as measured on day 120. Such d-AmB/PLGA injection was also effective in established lesions (day 30), leading to 97% parasite burden reduction, as compared with d-AmB or liposomal AmB (Ambisome®) i.l. injection containing the same AmB dose. Pharmacokinetic studies showed that following d-AmB/PLGA injection, AmB leaked slower from non-infected than infected ears, yet remaining in the ear tissue for as long as 30 days. Of interest, AmB was not detectable in the circulating plasma for at least two weeks of d-AmB/PLGA injection, contrasting with the rapid and durable (2 days) detection after free d-AmB injection. Despite the transient ear swelling and local cell infiltration, no alterations in AST, ALT and creatinine serum levels was induced by d-AmB/PLGA. For its approved components, local efficacy, and single-dose applicability, this novel and safe AmB microparticle depot formulation has strong potential as a new therapy for human CL. Graphical abstract: Image 1 Highlights: d-AmB/PLGA was more selectively active against intracellular parasites than d-AmB. A single ear injection effectively controlled established infections in mice. Tissue and plasma pharmacokinetics confirmed the local depot effect. Toxicological studies showed a transient local reaction, and no systemic toxicity. d-AmB/PLGA has strong potential as a novel local and single-dose therapy for human CL.